Effect Of Liquidity Ratio, Solvency, Activity, And Provability On The Company's Financial Performance (Empirical Study On Food And Beverage Industry Listed On Indonesia Stock Exchange Period 2020-2022) - Wulan Sulistyowati; Nursiam, Nursiam (Jurnal Ekonomi, 2024)
Abstrak: Financial performance is a process that must be done by the company because financial problems are one of the main issues concerning the survival of the company, therefore it is necessary to hold a professional handling in every operational activity to anticipate the occurrence of excess or shortage of funds that will lead to bankruptcy. This study is a quantitative study that aims to analyze the effect of liquidity ratios, solvency, activity, and profitability on the company's financial performance. The population of this study is food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. By using purposive sampling method then found 70 companies as a sample. The analytical methods used in this study are descriptive statistical analysis, classical assumption test, and multiple linear analysis. The results of this study indicate that the ratio of liquidity, activity, and profitability affect financial performance, while the solvency ratio does not affect financial performance.